Numerical evaluation of microwave thermal ablation to treat small adrenocortical masses. Issue 3 (9th January 2018) - Ruvio, Giuseppe; Eaton‐Evans, Jimmy; Shahzad, Atif; O'Halloran, Martin
Abstract: In this study, microwave thermal ablation is numerically evaluated in the context of a treatment for Conn's Syndrome. This condition is caused by a benign shallow tumor in the cortex of adrenal gland. The modeling and design of microwave applicator to deliver thermal ablation to the adrenal gland requires accurate tissue characterization. Measuring the dielectric properties of the constituent tissues in the adrenal gland, that is cortex and medulla, enables more accurate numerical modeling for electromagnetic and thermal simulations. This study presents an anatomically and dielectrically realistic numerical model of the adrenal gland, and investigates the feasibility of applying controlled heating to small targets in the adrenal cortex. In addition, the use of dielectric contrast between the fat and the cortex of the adrenal gland to focus the thermal energy in the gland has also been studied. Being conscious of limitations of numerical simulation of complex multi‐physics problems like the microwave ablative treatment, calculated results provide a preliminary description of the electromagnetic and thermal phenomena involved.